2015
DOI: 10.1002/oby.21174
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin differentially promotes development of a phenotypically distinct adipocyte

Abstract: ObjectiveEnvironmental endocrine disrupting chemicals (EDCs) are increasingly implicated in the pathogenesis of obesity. Evidence implicates various EDCs as being pro-adipogenic, including tributyltin (TBT), which activates the peroxisome proliferator activated receptor-γ (PPARγ). However, the conditions required for TBT-induced adipogenesis and its functional consequences are incompletely known.MethodsThe co-stimulatory conditions necessary for preadipocyte-to-adipocyte differentiation were compared between T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 42 publications
(59 reference statements)
8
48
0
Order By: Relevance
“…About 10 years ago, it was first proposed that some EDCs are putative obesogens, with properties that alter the control of adipogenesis and energy balance (Grün and Blumberg, 2006) and lead to increased body weight. Obesogenic EDCs include tributyltin, tolyfluanid, and DES (Grün and Blumberg, 2006; Newbold et al, 2007; Regnier et al, 2015). A body burden of EDCs is also predictive of metabolic disorders and obesity in human populations (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…About 10 years ago, it was first proposed that some EDCs are putative obesogens, with properties that alter the control of adipogenesis and energy balance (Grün and Blumberg, 2006) and lead to increased body weight. Obesogenic EDCs include tributyltin, tolyfluanid, and DES (Grün and Blumberg, 2006; Newbold et al, 2007; Regnier et al, 2015). A body burden of EDCs is also predictive of metabolic disorders and obesity in human populations (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Considering how many chemicals increase the commitment or differentiation of adipocytes, it is reasonable to ask whether the adipocytes produced are normal and fully functional . Such studies were prompted by the studies of Sargis and colleagues who investigated the effects of TBT vs the pharmaceutical PPARγ activator, troglitazone on the differentiation and function of 3T3‐L1 pre‐adipocytes, in vitro . TBT‐induced adipocytes produced lower levels of adiponectin and CEBPα mRNA and protein than did troglitazone‐induced adipocytes.…”
Section: Obesogen Exposure Can Produce Unhealthy Adipocytesmentioning
confidence: 99%
“…TBT‐induced adipocytes produced lower levels of adiponectin and CEBPα mRNA and protein than did troglitazone‐induced adipocytes. The TBT‐induced adipocytes displayed reduced GLUT4 expression but normal glucose uptake and they inferred that TBT had produced “unhealthy” adipocytes . White adipocytes play an important role in metabolic health by removing glucose from the circulation when stimulated by insulin .…”
Section: Obesogen Exposure Can Produce Unhealthy Adipocytesmentioning
confidence: 99%
“…Thereafter, a growing number of studies showed that exposure to TBTCl resulted in obesity, and hepatic steatosis in rodents . Moreover, one recent study in vitro showed that TBT reduced adiponectin expression . Adiponectin can counteract multiple manifestations of MS and serve as a valuable biomarker for MS .…”
Section: Introductionmentioning
confidence: 99%